Effect of exercise training on the cardiovascular and biochemical parameters in women with eNOS gene polymorphism - Rezende, Tiago M. [UNESP]; Sponton, Carlos H.G. [UNESP]; Malagrino, Pamella A. [UNESP]; Bezerra, Marcos A.C.; Penteado, Carla F.F.; Zanesco, Angelina [UNESP] (Taylor & Francis, 2011)
Context: Presence of endothelial nitric oxide synthase (eNOS) gene polymorphism has been associated with cardiovascular disease (CVD) whereas exercise training (EX) promotes beneficial effects on CVD which is related to increased nitric oxide levels (NO). Objective: To evaluate if women with eNOS gene polymorphism at position-G894T would be less responsive to EX than those who did not carry T allele. Methods: Women were trained 3 days/week, 40 minutes session during 6 months. Cardio-biochemical parameters and genetic analysis were performed in a double-blind fashion. Results: Plasma NOx - levels were similar in both groups at baseline (GG genotype: 18.44±3.28 μM) and (GT + TT genotype: 17.19±2.43 μM) and after EX (GG: 29.20±4.33 and GT+TT: 27.38±3.12 μM). A decrease in blood pressure was also observed in both groups. Discussion and conclusion: The presence of eNOS polymorphism does not affect the beneficial effects of EX in women. © 2011 Informa UK, Ltd.
Keywords: Blood pressure; Nitric oxide; Physical training; Women; endothelial nitric oxide synthase; nitric oxide; NOS3 protein, human; allele; biosynthesis; blood; blood pressure; Brazil; cardiovascular disease; case control study; double blind procedure; enzymology; exercise; female; gene frequency; genetics; genotype; human; middle aged; single nucleotide polymorphism; Alleles; Blood Pressure; Cardiovascular Diseases; Case-Control Studies; Double-Blind Method; Exercise; Female; Gene Frequency; Genotype; Humans; Middle Aged; Nitric Oxide; Nitric Oxide Synthase Type III; Polymorphism, Single Nucleotide